Japan in the Asia-Pacific Region and its Strategic Partnership with NATO - Siposné Kecskeméthy, Klára; Sipos, Alexandra (POLARITIES, 2026)
This paper examines Japan’s geopolitical position in the Asia-Pacific region and assesses its diversified partnership relations. Japan has a key geopolitical position in the Asia-Pacific, as a maritime power, a developed industrial economy, and a democratic state within the security framework led by the United States. Although traditionally constrained by its pacifist constitution, Japan is now pursuing a more proactive security policy under its Free and Open Indo-Pacific (FOIP) vision, which emphasizes regional stability, connectivity, and the rule of law. This transformation includes expanding defence capabilities and strengthening security partnerships. Japan makes significant efforts to broaden its strategic partnerships. While the U.S.-Japan alliance remains the cornerstone of Tokyo’s security strategy, its close cooperation and deepening ties with NATO have also become increasingly important. Developments in Europe and the Asia-Pacific are closely interconnected, especially given the systemic challenges posed by an increasingly assertive China, tensions on the Korean Peninsula, and pressures from the Russian Federation. The paper discusses Japan’s ongoing transformation in reshaping the Asia-Pacific balance, positioning the country as a more proactive security and diplomatic actor, one that must balance its national interests, alliance commitments, and its vision for a stable, rules-based Indo-Pacific order.